Exogenous melatonin improved photosynthetic efficiency of photosystem II by reversible phosphorylation of thylakoid proteins in wheat under osmotic stress - Lin, Shuai; Song, Xiao-Fang; Mao, Hao-Tian; Li, Shuang-Qing; Gan, Jie-Ying; Yuan, Ming; Zhang, Zhong-Wei; Yuan, Shu; Zhang, Huai-Yu; Su, Yan-Qiu; Chen, Yang-Er (Frontiers in Plant Science, 2022)
It has been well demonstrated that melatonin plays an important protective role in photosynthesis of plants under various environmental stresses, while the detailed mechanisms by which melatonin protects photosystem II (PSII) under environmental stress are still unclear. In the study, the effects of melatonin on photosynthetic efficiency, energy dissipation, PSII protein composition, and reversible phosphorylation of thylakoid proteins were investigated in wheat plants under osmotic stress. The results showed that osmotic stress significantly reduced pigment content, photochemical efficiency of PSII, oxygen-evolving activity, and dissipation of excess excitation energy, while 25 μM melatonin applications greatly alleviated their decline under osmotic stress. Western blot data of PSII proteins revealed that melatonin upregulated the levels of D1, Lhcb5, Lhcb6, PsbQ, and PsbS proteins in wheat exposed to osmotic stress. In addition, thylakoid membrane proteins were strongly phosphorylated in wheat under osmotic stress with or without melatonin. Furthermore, the results from PSII protein dephosphorylation showed that exogenous melatonin promoted the dephosphorylation of LCHII, CP43, and D1 under osmotic stress. Therefore, our findings suggest that melatonin can provide an effective protection for the photosynthetic apparatus by the regulation of PSII proteins and the reversible phosphorylation of thylakoid proteins under drought stress.